Indonesia Agro-Value Chain Assessment : Issues and Options in Promoting Digital Agriculture - World Bank (World Bank, Washington, DC, 2020)
This background paper aims to provide an assessment of the issues and options in promoting digital agriculture in Indonesia, within the broader technology landscape of the country, with the primary aim of informing the design of the proposed World Bank investment project. The study considers global best practices as well as the status of Indonesia in product traceability, e-commerce, agriculture fintech service providers, weather index insurance providers, and precision farming technology providers. Although digital agriculture is cross-cutting across all commodities, the focus was on the horticulture and small ruminant value chains as those were identified as priority commodity categories by the Ministry of Agriculture. The study also offers high-level recommendations for policymakers on reforms and programs that can accelerate the adoption of digital agriculture. In the first section, the national context and the importance of ICT technology in agriculture are summarized. Section two presents the current landscape of digital agriculture in Indonesia, followed by section three that suggests key areas where ICT can play a role in agriculture, based on global experience. As scaling up the digitization of the agriculture sector involves a complex set of policy, investment, innovation, and capacity-building measures, several high-level recommendations are provided for policymakers and practitioners in the fourth and last section.